A comparison using Faraday cups with 1013 Ω amplifiers and a secondary electron multiplier to measure Os isotopes by negative thermal ionization mass spectrometry. (4th September 2017) - Wang, Guiqin; Sun, Tiantian; Xu, Jifeng
Abstract : Rationale: According to the Johnson‐Nyquist noise equation, the value of electron noise is proportional to the square root of the resistor value. This relationship gives a theoretical improvement of 100 in the signal/noise ratio by going from 10 11 Ω to 10 13 Ω amplifiers for Faraday detection in thermal ionization mass spectrometry (TIMS). Methods: We measured Os isotopes using static Faraday cups with 10 13 Ω amplifiers in negative thermal ionization mass spectrometry (NTIMS) and compared the results with those obtained with 10 11 Ω amplifiers and by peak‐hopping on a single secondary electron multiplier (SEM). We analysed large loads of Os (1 μg) at a range of intensities of 187 OsO3 (0.02–10 mV) in addition to small loads of Os (5–500 pg) to compare the results of the three methods. Results: Using 10 13 Ω amplifiers, the long‐term reproducibility determined from Merck Os was 187 Os/ 188 Os = 0.1211 ± 0.0086 and 0.120229 ± 0.000034 at 0.02 mV and 10 mV of 187 OsO3 intensities. Meanwhile, the analysed JMC Os loadings of 5 and 500 pg showed 187 Os/ 188 Os = 0.10669 ± 0.00036 and 0.106807 ± 0.000023. In comparison, the values measured by the SEM were 187 Os/ 188 Os = 0.10704 ± 0.00056 and 0.10690 ± 0.00013. All errors are in 2 standard deviation (SD). Conclusions: Both the accuracy and the precision determined using the 10 13 Ω amplifiers and the SEM are identical when the Os amounts are within 10–50 pg. However, the former analysis time can be shortened by approximately two‐thirds. The SEM measurement is still the most precise method for Os amounts <10 pg, but the analyses using 10 13 Ω amplifiers suggest they are significantly better than the SEM for Os amounts >50 pg.